Diseases and Remedies of Al-Kibr in the Light of Uthman bin Foduyeâs Shifaâ al-Nufus - Gokaru, Shuaibu Umar; Matzin, Aizan Ali @ (INSANCITA, 2016)
ABSTRACT: This research aims at finding out the remedies for the disease of arrogance/pride that has been rampant among the people in contemporary Muslim world, particularly Nigerian Muslim society. The analysis is not on words and terms, but rather on meaning and ideas with analysis and explanations given by the âMufassirunâ and other scholars. âUthman bin Foduye emerged in nineteenth-century with the mission to revive the Sunnah, and to eradicate innovations in Hausaland (West Africa) caused by the deviant teachings. This is the reason why he wrote on spiritual diseases in his book related to healing of the soul. âUthman bin Foduye was influenced by al-Ghazali and particularly his book on âIhyaâ âUlum al-Dinâ (Revival of the Religious Sciences). He wrote this treaty in order to make it easier for the people to know the destructive evils of the heart, so as to do what Allah loves and accepts, since pride is one of the attributes of Allah alone. The appearance of the British destroyed the Sokoto Caliphate in Northern-Nigeria and burnt many of Uthman bin Foduyeâs books, including the âShifa al-Nufusâ (Healing of the Soul), for fear that his works will inspire his followers people to rise against the oppressors. KEY WORD: Diseases and remedies, arrogance and pride, Uthman bin Foduye, healing of the soul, al-Ghazali, revive the Islam, West Africa, British, and rise against the oppressors.ABSTRAKSI: âPenyakit dan Pengubatan Al-Kibr (Kesombongan/Kebanggaan Diri) dalam Cahaya Shifa al-Nufus (Penyembuhan Jiwa)-nya Uthman bin Foduyeâ. Kajian ini mau mencari tahu ubat bagi penyakit sombong/bangga diri yang telah berleluasa di kalangan rakyat di dunia Islam masa kini, terutamanya masyarakat Islam Nigeria. Analisis ini tidak disenaraikan dalam kata-kata dan istilah, tetapi pada makna dan idea dengan analisis dan penjelasan yang diberikan oleh Mufassirun dan ulama yang lain. Uthman bin Foduye muncul pada abad ke-19 dengan misi untuk menghidupkan semula Sunnah, dan untuk membasmi amalan bidâah di Hausaland (Afrika Barat) yang disebabkan oleh ajaran sesat. Ini adalah sebab mengapa dia menulis mengenai penyakit rohani dalam bukunya bersabit penyembuhan jiwa. Uthman bin Foduye dipengaruhi oleh al-Ghazali dan terutamanya buku âIhya Ulum al-Dinâ (Kebangkitan Ilmu-ilmu Agama). Beliau menulis risalah ini untuk membuat ianya lebih mudah bagi rakyat supaya tahu keburukan yang merosakan hati, untuk melakukan apa yang Allah suka dan menerima, kerana kebanggaan diri setakat milik Allah semata-mata. Kemunculan British telah menghancurkan Khilafah Sokoto di wilayah Utara-Nigeria dan British pula telah membakar banyak buku karangan Uthman bin Foduye, termasuk âShifa al-Nufusâ, kerana British takut bahawa karya-karya Uthman bin Foduye ini akan memberi inspirasi kepada para pengikut dan kaumnya untuk bangkit melawan para penindas.KATA KUNCI: Penyakit dan pengubatan, sombong/bangga diri, Uthman bin Foduye, penyembuhan jiwa, al-Ghazali, menghidupkan semula Islam, Afrika Barat, British, dan bangkit melawan penindas.Â Â About the Authors: Shuaibu Umar Gokaru is a Lecturer at the Department of Islamic Studies, Faculty of Arts and Education BSU (Bauchi State University) in Gadau, Nigeria; and Ph.D. Candidate at the Department of Islamic History and Civilization, Academy of Islamic Studies UM (University of Malaya), 50603 Kuala Lumpur, Malaysia. Dr. Aizan Ali @ Matzin is a Senior Lecturer at the Department of Islamic History and Civilization, Academy of Islamic Studies UM (University of Malaya), 50603 Kuala Lumpur, Malaysia. E-mails address: gokarushuaibu@gmail.com and aizan@um.edu.myHow to cite this article? Gokaru, Shuaibu Umar & Aizan Ali @ Matzin. (2016). âDiseases and Remedies of Al-Kibr in the Light of Uthman bin Foduyeâs Shifaâ al-Nufusâ in INSANCITA: Journal of Islamic Studies in Indonesia and Southeast Asia, Vol.1(1), February, pp.67-80. Bandung, Indonesia: Minda Masagi Press, ISSN 2443-1776.Chronicle of the article: Accepted (June 4, 2015); Revised (November 10, 2015); and Published (February 5, 2016).